Extracting Buildings from Aerial Images Using Hierarchical Aggregation in 2D and 3D - Fischer, André; Kolbe, Thomas H.; Lang, Felicitas; Cremers, Armin B.; Förstner, Wolfgang; Plümer, Lutz; Steinhage, Volker (Computer vision and image understanding, 1998)
We propose a model-based approach to automated 3D extraction of buildings from aerial images. We focus on a reconstruction strategy that is not restricted to a small class of buildings. Therefore, we employ a generic modeling approach which relies on the well-defined combination of building part models. Building parts are classified by their roof type. Starting from low-level image features we combine data-driven and model-driven processes within a multilevel aggregation hierarchy, thereby using a tight coupling of 2D image and 3D object modeling and processing, ending up in complex 3D building estimations of shape and location. Due to the explicit representation of well-defined processing states in terms of model-based 2D and 3D descriptions at all levels of modeling and data aggregation, our approach reveals a great potential for reliable building extraction.